'Palliative care equals end-of-life care': barriers to referral in a paediatric tertiary care centre. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Twamley, Katherine; Kelly, Paula; Craig, Finella; Hollowell, Delia Rizpah; Mendoza, Patricia; Bluebond-Langner, Myra
Abstract : Background: Referral rates to children's palliative care services are consistently low and occur late in the illness trajectory. Previous studies cite healthcare professionals' (HCP) attitudes and knowledge as barriers to referral. The majority of these studies were conducted in the US, where differences in palliative care services limit the applicability of findings to the UK. This paper presents the first ever survey of UK paediatric HCPs' knowledge and attitudes towards paediatric palliative care. Aim: To describe attitudes towards palliative care and knowledge of services among HCPs working in a paediatric tertiary care hospital in the UK, and to consider their role in referrals. Methods: A survey of closed and opened-ended questions was sent to 923 HCPs in a large paediatric tertiary care hospital. Descriptive statistical analyses were conducted with SPSS, and thematic analysis of open-ended responses with NVIVO software. Results: 132 HCPs responded (14% response rate) including 60 nurses, 42 physicians and 30 other HCPs. HCPs were most likely to choose 'diagnosis' as the appropriate time to refer a patient to palliative care (48%); only 4% selected the end of life period. 63% disagreed with the statement 'Palliative care is primarily about providing care at the end of life.' Yet the most frequently reported reason for previous palliative care referrals was to 'discuss with parents the option of the child dying at home or in a hospice' (49%); 50 % of those completing the open text response box indicated that they associated palliative care with end-of-life care and dying. Conclusions: Our data suggest that given the HCPs' awareness of the principles of palliative care and knowledge of services, more attention needs to be given to HCPs' underlying association of palliative care with end-of-life. Other factors may also play a role in referral and require further research and consideration.